The Effects of Microseconds Electroporation on Pore Size, Viability and Mitochondrial Membrane Potential of Cervical Cancer Cells - Güney GÜRSOY; Meriç Arda ESMEKAYA; Zehra ÇİÇEK (Bezmiâlem Science)
Objective: Electroporation (EP) is a method in which the membrane permeability is increased by applying electrical pulses. The determination of modifications that occur in cells subsequent to EP with varying pulse parameters holds significant importance in establishing the foundations of EP theory. Therefore, we sought clarification regarding the phenomenon of pore formation on the membrane of the electroporated human cervical cancer cell line (HeLa) cells. Methods: The pores created on the cell membrane due to EP was observed using a scanning electron microscope. The change in the viability and mitochondrial membrane potential (ΔΨm) of cells was determined by WST-8 and JC-1 assays. Results: The surface of the electroporated cell membrane exhibited a relatively uniform pore population. The viability of HeLa cells was significantly reduced with increasing electric field intensities. A slight decrease in ΔΨm was observed between the control and the 0.8 and 1.6 kV/cm EP groups, but ΔΨm was higher in the 2.4 and 3.2 kV/cm EP groups compared to the control group. Conclusion: In conclusion, our study showed that the application of EP to the cervical cancer cell line resulted in the formation of pores of varying sizes on the membrane. While cell viability decreased with increasing electric field amplitude, no significant change was observed in ΔΨm between EP treatment and control groups. It should be noted that further research is needed to determine the pore distributions in electroporated cells and the resulting changes at different electric field amplitudes.